“Técnica de Oxford para fortalecimiento muscular en adultos con tendinitis bicipital. Centro de Rehabilitación Física del GAD Municipal Chambo. 2018” - Buñay Jaya, Edy Fernando (2019)
This research work was the result of the approach of the authors, based on the help to the community, in this case to adult patients from the Physical Rehabilitation Center of the Chambo Municipal GAD who present biceps tendonitis. The main objective of this research work was to verify the efficacy of the Oxford technique for muscle strengthening in adults with biceps tendonitis. The study method used was of non-experimental design, the type of research was descriptive, explanatory and applicative, with a population of 23 patients, whose care was daily. A diagnostic medical history was used for data collection. The present investigative work shows that of the total of the analyzed population that were 80 patients, a 28.75% presents bicipital Tendonitis, pathology to be studied. The Daniel's test was used to determine the influence of the technique on the force, which was applied before and after the accomplishment of the technique. The first test resulted in 39% of patients presenting grade 3; 52% degree 4 strength, 9% grade 5 muscle strength. In comparison with the final test after applying the technique, 78% of the patients reached Grade 5, 22% obtained Grade 4 in the Daniel's Test. In this investigation it was concluded that by applying the Oxford technique, muscle strength was increased in patients of the Physical Rehabilitation Center of the Chambo Municipal GAD, verifying its effectiveness for muscle strengthening.